In vitro propagation of dalbergia latifolia roxb. through tissue culture - Khages Chandra Mahato (College of Forestry, 1992)
In investigations carried out in the College of Forestry, Vellanikkara during 1989 – 92, it was found that nodal segments of 1.5 cm length were ideal as the explants. Prophylactic spraying of the mother tree with the systemic fungicides Bavistin and the contact fungicide Dithane M-45 coupled with surface sterilization of explants with mercuric chloride 0.1 per cent for 12 minutes fully controlled contamination of the culture. Both woody plant medium (WPM) and Murashige and Skoog (MS) medium were found to be suitable for the primary culture establishment from the explants. While WPM supplemented with kinetin 1.0 ppm and IAA 0.1 ppm was most suitable for inducing healthy single shoots in about 80 per cent of the explants, MS along with BA 2.0 ppm or BA 0.25 ppm and CH 1000 mg 1-1 induced maximum number of multiple shoots (up to 25). Among the various media supplements tested, adenine sulphate was found to be capable of inducing multiple shoots and CH increased the rate of shoot multiplication. Coconut water did not show any beneficial effects. Liquid cultures with shaking at initial periods prolonged the life of the primary culture up to six months with continuous production of shoots. Continuous culture was developed using nodal segments of shoots derived from the primary cultures. The most suitable medium for this was found to be MS supplemented with kinetin and BA 0.5 ppm each. The best in vitro rooting was achieved by resorting to a pulse treatment of the shoots with IBA (1000 ppm) and culturing them in vermiculite + sand medium. Up to 100 per cent rooting could be achieved by this method. In vivo rooting was obtained by transferring the shoots after IBA treatment to vermiculite under high humidity conditions. Planting out and hardening of the in vitro rooted plantlets was carried out in soilrite. Up to 90 per cent survival could be achieved. The hardened plantlets were acclimatized in polythene bags with ordinary potting mixture and after 16 weeks they were field planted. The cost of production of one plantlet including hardening was worked out to Rs. 4.47.